Autonomous Learning in Higher Education Students: A Systematic Review of The Literature On Wos Between 2019-2022 - Mares-Ruiz, Carlos Martín; Cardoza-Sernaqué, Lizbany Sujey; Jiménez-Jáuregui, Yadira Julia; Belleza-Torrejón, Sofía Emilce; Salas-Torres, Lissette Margarita; Peláez-Valdivieso, José Víctor (International Journal of Membrane Science and Technology, 2023)
In higher education, autonomous learning is the capacity that students develop from the combination of a series of affective, social, cognitive and metacognitive factors that allow students to self-regulate their learning. In this context, the present study aims to systematize the evidence from the scientific literature in relation to autonomous learning in higher education students. The PRISMA 2020 method was used for the phase of identification of records in the WoS (Web of Science) database during the period 2019-2022, which allowed the identification of 8,339 studies, and from the application of data exclusion criteria, 13 were selected. studies whose purpose was to answer the research question: What skills do higher education students use to develop autonomy in their learning? The data was systematized based on the authors, countries of publication according to the origin of the journal, keywords, dimensions, instruments used, application strategies and conclusions of the studies to analyze possible patterns, similarities and characteristics that can be contrasted with others. studies to identify possible strengths or weaknesses regarding autonomous learning in higher education students. The results show that Spanish journals lead in content on the subject. Likewise, there is a wide variety of keywords such as: higher education, academic self-regulation, learning strategies, etc. In addition, 84.6% of the studies used questionnaires for the development of their research. It is concluded that, according to the content of the studies, it is important to highlight that the use of ICT and teaching support are important to promote the self-regulation of the learning of university students, as well as to highlight that, through pedagogical mediation, Through counseling, tutorials and teaching support, it facilitates the development of planning skills, concentration, motivation and reflection on the learning of higher education students.